Microglia depletion leads to increased susceptibility to ocular hypertension-dependent glaucoma - Diemler, Cory A.; MacLean, Michael; Heuer, Sarah E.; Hewes, Amanda A.; Marola, Olivia J.; Libby, Richard T.; Howell, Gareth R. (Frontiers in Aging Neuroscience, 2024)
In recent years, microglia have been highlighted for playing integral roles in neurodegenerative diseases, like glaucoma. To better understand the role of microglia during chronic ocular hypertension, we depleted microglia from aged (9–12 months old) DBA/2 J (D2) mice, which exhibit age-related increases in intraocular pressure, using a dietary CSF1R antagonist, PLX5622. Retinal ganglion cell (RGC) somas were counted, and optic nerve cross-sections stained and assessed for glaucomatous damage. Sustained administration of dietary PLX5622 significantly reduced the numbers of retinal microglia. Dietary PLX5622 did not lead to changes in intraocular pressure in D2 or normotensive DBA/2 J-Gpnmb+ (D2-Gpnmb+) control mice. While PLX5622-treated D2-Gpnmb+ did not develop optic nerve damage, PLX5622-treated D2 mice showed a significant increase in moderate-to-severe optic nerve damage compared to D2 mice fed a control diet. In conclusion, global reduction of microglia exacerbated glaucomatous neurodegeneration in D2 mice suggesting microglia play an overall beneficial role in protecting from ocular hypertension associated RGC loss.